INTEGRATED FINANCIAL MANAGEMENT INFORMATION SYSTEM, PROCUREMENT PERFORMANCE AND CUSTOMER SATISFACTION IN THE COUNTY GOVERNMENT OF NYERI - Mwangi, Peter Gitau; Kiarie, Dr. David; Kiai, Dr. Richard (International Journal of Supply Chain Management, 2018)
Purpose: The purpose of this study was to evaluate the customer satisfaction due to IFMIS adoption and procurement performance in the county government of Nyeri. Methodology: Descriptive research design was adopted. Respondents in the study comprised of suppliers and staff of Nyeri county Government. A self-administered questionnaire was use to collect data. Descriptive and regression analysis were used. Results: Descriptive data analysis results indicate that the implementation of IFMIS had not led to customer satisfaction at the county government of Nyeri. At 5% level of significance the regression results indicated a positive but insignificant relationship between customer satisfaction and procurement performance with Î²=0.021 at p value 0.911 which is greater than 0.05 Unique contribution to theory, practice and policy: This study recommends that the National Treasury and ICT Ministry should undertake joint research into the most feasible platform to host IFMIS. This study recommends that the county government should liaise with the IFMIS capacity building department at national level to localize training programmes for staff, committee members, Members of County Assembly and the general public. The county government should come up with policy to ensure that stakeholder capacity building is developed to enhance diffusion of IFMIS technology. Institutional capacity was found to play a vital role procurement performance. The county government of Nyeri had laid the requisite infrastructure, though software challenges abound. This study recommends that the county government should seek designers in IT to get the best information of the systems and also lay down effective legislature on IFMIS procedures that ensure proper financial management at all levels Keywords: IFMIS, procurement performance, customer satisfaction